Multilayer Structuring of Nonleaded Metal (BiSn)/Polymer/Tungsten Composites for Enhanced γ‐Ray Shielding. Issue 6 (9th February 2020) - Kim, Hoyeon; Lim, Junyoung; Kim, Jihun; Lee, Jungil; Seo, Yongsok
Abstract : To effectively attenuate unrecognized and/or unwanted exposures to high‐energy γ‐rays which leads to occupational hazards when accumulated in a wide range of industries, nonleaded metal (bismuth(Bi)‐tin(Sn))/polymer and tungsten (W) composites are prepared and tested. A eutectic alloy, BiSn, with a low melting temperature of 139 °C, is applied for the first time to prepare a γ‐ray shielding material. Compounding of the BiSn alloy/polymer is conducted in a twin screw mixer/extruder by exploiting the alloy's low melting temperature. Multilayer BiSn/polymer composites are prepared by pressing the extruded composites. The γ‐ray shielding efficiency of the composite is elucidated on the basis of the K‐edge theory. To make a thinner but more efficient composite, W flakes are laminated onto the BiSn/polymer composite sheet. The produced (BiSn/polymer)/W composite sheet exhibits strong attenuation of γ‐rays, which is found to follow the Beer–Lambert law. A multilayer (BiSn/polymer)/W laminate can offer both a sufficient thickness with flexibility and an effective shielding against γ‐rays to meet the requirements for protective clothing or protective equipment. This work demonstrates that (BiSn/polymer)/W laminates can be used as a reliable Pb‐substitution material to protect the human body from the high‐energy γ‐rays. Abstract : To protect from the unrecognized and/or unwanted exposures to high‐energy γ‐rays, nonleaded metal (bismuth(Bi)‐tin(Sn))/polymer and tungsten (W) composites are prepared and tested. A multilayer (BiSn/polymer)/W laminate can offer both a sufficient thickness with flexibility and an effective shielding against γ‐rays to meet the requirements for protective clothing or protective equipment.